1995
DOI: 10.1007/bf00169334
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by suramin and reactive blue 2 of GABA and glutamate receptor channels in rat hippocampal neurons

Abstract: Effects of suramin and reactive blue 2 (RB2), compounds known as antagonists at P2-purinoceptors, on ionic currents mediated through GABA and glutamate receptor channels were investigated in rat hippocampal neurons. Under whole-cell voltage-clamp, suramin (30 to 300 microM) and RB2 (10 to 100 microM) inhibited a current activated by 10 microM GABA in a concentration-dependent manner. Suramin (100 and 300 microM) and RB2 (10 and 30 microM) also inhibited an inward current activated by kainic acid (100 microM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 28 publications
5
43
4
Order By: Relevance
“…However, this does not alter our interpretations, as we did not observe a consistent or signi¢cant augmentation of the e¡ects of ATP when suramin was microinjected into the VLM. Although non-speci¢c e¡ects of suramin have been reported in rat hippocampal neurones in culture (Nakazawa et al, 1995), suramin did not block responses to glutamate in the present study.…”
Section: Nsc 5204 5-11-01contrasting
confidence: 83%
“…However, this does not alter our interpretations, as we did not observe a consistent or signi¢cant augmentation of the e¡ects of ATP when suramin was microinjected into the VLM. Although non-speci¢c e¡ects of suramin have been reported in rat hippocampal neurones in culture (Nakazawa et al, 1995), suramin did not block responses to glutamate in the present study.…”
Section: Nsc 5204 5-11-01contrasting
confidence: 83%
“…The first remains the inadequacy of the antagonists available. It must be stressed that, at the concentrations used in many experiments (Ͼ30 M), suramin, PPADS, and reactive blue 2 have been shown to block currents elicited by kainate, NMDA, and GABA in dissociated cells (328) and to slow the rate of rise of currents elicited by AMPA (165). A second complication is that evoked synaptic currents are often observed in only a fraction of neurons tested, and this may make it difficult to carry out the critical comparative studies in tissues from mice in which P2X receptor subunits have been knocked out.…”
Section: Endogenous Atpmentioning
confidence: 99%
“…There are also reports that suramin inhibits glutamatergic synaptic transmission (Motin and Bennett, 1995;Gu et al, 1998) and whole-cell currents mediated by AMPA receptors (Nakazawa et al, 1995;Zona et al, 2000) and NMDA receptors (Ong et al, 1997;Peoples and Li, 1998). Suramin was observed to inhibit binding of radioligands to NMDA receptors (Balcar et al, 1995) but not kainate receptors (Ong et al, 1997), which suggested some selectivity among glutamate receptors.…”
mentioning
confidence: 89%